Finite-Difference Time-Domain Simulations of Radon Transport in Porous Media - A. Tayebi; H. Bezzout; M. El Maghraoui; H. El Faylali (PPIKSN-BATAN, 2020)
In this work, an efficient algorithm, using a finite-difference time-domain (FDTD) technique, is proposed for modeling the variation of radon concentration as a function of soil structure parameters and vice versa. The development of the FDTD model is based on the simultaneous resolution of the radon transport equation in a porous, homogeneous medium, namely the soil. This equation describes the concentration of radon per pore volume unit. The numerical results are compared with those of the literature or with the theoretical ones.